Local and intermediated-intensity soil disturbances increase the colonization and expansion dynamics of an invasive plant in Southern Patagonian rangelands - Rauber, Ruth Bibiana (2014)
Disturbances are important drivers in natural ecosystems, affecting the vegetation structure and functioning. Invasions of exotic plant species are often associated to disturbances in a complex manner, because they depend on the type, intensity,spatial and temporal arrangement of disturbances, and the particular abiotic and biotic context. Field studies that evaluate the dynamics of plant invasions under different disturbance regimes have a great importance for the understanding of the disturbance effects on invasion spread. In this work we evaluated, through a field manipulative experiment, the early colonization and expansion dynamics of an aggressive invader of grasslands, Hieracium pilosella L., under two disturbance types. We used a split-plot experiment by crossing three levels for a local, sporadic, of increasing intensity disturbance [i.e., 1- undisturbed, 2- vegetation mowing, and 3- ploughing], within two levels for an extensive and chronic disturbance (i.e., grazed and ungrazed). In the range of intensities of disturbance evaluated, the intermediate intensity (i.e., mowing) accelerated the colonization when it is grazed and the expansion of H. pilosella in ungrazed condition. In contrast, lower and higher intensity disturbances, such as ungrazed and ploughing treatments decelerated both invasion processes. Changes in resource availability, interspecific competition and particular characteristics of the invader, i.e., high light requirements, prostrate growth and the presence of stolons, could explain these early invasion patterns.